Deponent verbs and middle-voice nouns in Temiar - Benjamin, Geoffrey (2011)
The infix -a- in Temiar (Central Aslian, Peninsular Malaysia) covers a wide range of functions, both productive and non-productive. In Temiar morphology generally it serves iconically to indicate an embedded object. As a productive infix, it forms the middle voice of verbs and the singular of human nouns (Benjamin, in press). The main nonproductive function of -a- is as a frozen infix in (1) a set of non-inflecting 'deponent' verbs and (2) a set of disyllabic ('middle-voice') nouns. The same semantic dimension underlies both, namely that the verbs and nouns in question indicate that the subject or entity is thought of as being simultaneously its own agent and patient. Culturally, the special attention paid to 'middle-voice' processes relates to a central Temiar interest in the specifically dialectical character of Self–Other relations.